Evaluating Pain Assessment in Emergency Care: A Systematic Review - Jadmiko, Arief Wahyudi; Romadlon, Debby Syahru (Jurnal Berita Ilmu Keperawatan, 2026)
Effective pain assessment in emergency departments (EDs) is essential to optimizing patient care and improving outcomes such as satisfaction, reduced hospitalization, and lower re-admission rates. This evidence-based critical review aims to explore the relationship between pain assessment practices in EDs and resulting patient outcomes. A systematic search was conducted across three electronic databases—PubMed, Google Scholar, and Web of Science—using the keywords "Emergency department AND Pain assessment AND Patient outcomes” using a structured PICO approach: Population (P) – ED patients, Intervention (I) – pain assessment, Control (C) – none, Outcome (O) – positive clinical and satisfaction-related outcomes. Inclusion criteria comprised original research articles published in English between 2005 and 2025 that focused on pain assessment in emergency settings and reported outcomes such as patient satisfaction, readmission rates, or clinical improvements. Exclusion criteria included non-English publications, studies outside the ED context, and non-original research. Article selection involved initial identification, duplicate removal, title/abstract screening, and full-text eligibility assessment. Out of 21,317 retrieved articles, 6,957 unique records remained after duplicate removal. The studies involving a total of 54,511 patients. Findings demonstrated that structured pain assessment and timely analgesic intervention led to significantly improved patient satisfaction, reduced emotional distress, better adherence to medical instructions, decreased rates of hospitalization, a higher likelihood of administration potent pain medication, ED Length of Stay, ED charges, and ED revisits. This review reinforces the vital role of effective pain assessment in emergency care settings. Evidence indicates that structured and timely pain management not only enhances patient comfort but also contributes to better clinical outcomes, higher satisfaction, and reduced healthcare utilization.